Towards integrated reporting : accounting change in the public sector - Katsikas, Epameinondas; Rossi, Francesca Manes; Orelli, Rebecca L. (Springer, 2017)
This book focuses on the accounting change processes that drive integrated reporting in the public sector. The Integrated Report is a tool that allows public sector entities to quantify and convey those aspects of their organization, strategy, governance and performance that lead to the creation of public value over time. To be successfully introduced, integrated reporting must follow a specific path of accounting change. The context in which public sector entities operate, and the unique relationship between the public sector and the environment, redefine the accounting process of change to deliver an integrated report. The authors provide a fresh look at integrated reporting on the basis of the accounting change processes that drive it, helping academics and practitioners to gain a deeper understanding of the challenges and benefits in terms of public value creation.
Keywords: Accounting.; Corporation reports.; elektronické knihy; electronic books